Total recall (1990) [videorecording (DVD)] - Verhoeven, Paul, 1938-; Schwarzenegger, Arnold; Ticotin, Rachel; Stone, Sharon, 1958-; Ironside, Michael, 1950-; Cox, Ronny; Dick, Philip K. (Artisan Home Entertainment, 2001)
In the year 2084 a worker leaves Earth for the mind-bending nightmarish reality of a Martian mining colony ruled over by a dictator who can alter reality to suit his whims.